Ambiguities of Interpretation: Translating the Late Celan - Nicholas J. Meyerhofer (Studies in 20th & 21st Century Literature, 1983)
Celan's later poems are seen as increasingly problematic because of their inherent tension between speaking and not speaking, because of their formalization (semantic and syntactic) of this tension, and also because of Celan's poetic intentionality. The latter, described as a poetics of ambiguity, is the focus of this article. Particular attention is given to the implications such a poetics has for the task of the (English) translator. To illustrate in the concrete this poetics, and to show how its intentional integration of thematic and etymological ambiguity must be taken into account by the translator, two late lyrics ("Einkanter: Rembrandt" and "Wenn ich nicht weiss") are translated and examined in detail.
Keywords: Celan; speaking; not speaking; semantic; syntax; syntac; poem; poetry; intentionality; ambiguity; poetics; translator; English; etymological ambiguity; & quot; Einkanter: Rembrandt& quot; Wenn ich nicht weiss; German poetry; German